Performing the divine mediums, markets and modernity in urban Vietnam - Endres, Kirsten W. (Copenhagen : NIAS Press ; Abingdon : Marston [distributor], 2011)
"Vietnam in the last two decades has experienced not only market reform and significant economic growth but also a related, symbiotic revival of popular religion. It is no surprise, then, that popular beliefs and rituals that once were attacked as wasteful and superstitious have again become a conspicuous feature of contemporary urban and rural life. A new blossoming of spirit mediumship has been part of this revival, not least that involving ritual possession by the deities of the Four Palace Pantheon, which this study based in urban Hanoi brings to life with a deft handling of complex theory, historical research, ethnographic material and analysis. This is indeed a sojourn into the world of mediumship in contemporary urban Vietnam - a spirited world full of colour, laughter, music and ritual dance that operates according to its own rules and principles - but it is also an insightful study of spirituality, performance, gender and heritage, one that highlights the fluidity of ritual practice and contestations of ritual performance among practitioners."--Publisher's website.
Introduction : inviting the spirits -- Personal fate and spirit identities -- Performing the divine -- Negotiating the rules of proper performance -- The (gendered) world of mediumship -- The heritagisation of Four Palace mediumship -- Epilogue : return to the realm.
Includes bibliographical references (p. 207-226) and index.
Description based on print version record.
Keywords: Mediums -- Vietnam; Spirit possession -- Vietnam; Vietnam -- Religious life and customs; Vietnam -- Religion -- Economic aspects; Religion; Ritual; Vietnam; RELIGION / Eastern; Electronic books